2010
DOI: 10.1038/pcan.2010.23
|View full text |Cite
|
Sign up to set email alerts
|

ERG oncoprotein expression in prostate cancer: clonal progression of ERG-positive tumor cells and potential for ERG-based stratification

Abstract: Gene fusions prevalent in prostate cancer (CaP) lead to the elevated expression of the ERG proto-oncogene. ERG activation present in 50–70% of prostate tumors underscores one of the most common oncogenic alterations in CaP. Despite numerous reports of gene fusions and mRNA expression, ERG oncoprotein status in CaP still remains to be defined. Furthermore, development of ERG protein-based assays may provide a new dimension to evaluation of gene fusions involving diverse androgen-regulated promoters and the ERG … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

33
236
8

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 219 publications
(277 citation statements)
references
References 27 publications
33
236
8
Order By: Relevance
“…The following clones and primary antibodies were used: anti-ERG rabbit monoclonal antibody (1:100 dilution, clone EPR3864, Abcam, Cambridge, MA, USA) 21 and anti-ERG mouse monoclonal antibody (1:1000 dilution, CPDR ERG-MAb, clone 9FY, CPDR, Rochville, MD, USA). 19 Dilution was Figure 1. A lymph node metastasis of an ERG-rearranged prostate cancer (PCa) (arrowheads) stained using the mouse monoclonal anti-ERG antibody (ERG-MAb) (a) and the rabbit ERG-MAb (b), respectively.…”
Section: Ihcmentioning
confidence: 99%
See 1 more Smart Citation
“…The following clones and primary antibodies were used: anti-ERG rabbit monoclonal antibody (1:100 dilution, clone EPR3864, Abcam, Cambridge, MA, USA) 21 and anti-ERG mouse monoclonal antibody (1:1000 dilution, CPDR ERG-MAb, clone 9FY, CPDR, Rochville, MD, USA). 19 Dilution was Figure 1. A lymph node metastasis of an ERG-rearranged prostate cancer (PCa) (arrowheads) stained using the mouse monoclonal anti-ERG antibody (ERG-MAb) (a) and the rabbit ERG-MAb (b), respectively.…”
Section: Ihcmentioning
confidence: 99%
“…So far, two monoclonal ERGspecific antibodies (that is, mouse monoclonal anti-ERG antibody (ERG-MAb) and rabbit ERG-MAb) have been established on prostatic tissues. Furusato et al 19 reported a highly specific mouse ERG-MAb performing a comprehensive evaluation of ERG protein expression using whole mount prostate sections from 132 PCa cases. The ERG protein expression pattern showed a strong concordance with ERG fusion transcripts by branched DNA assay or ERG rearrangement by fluorescence in-situ hybridization (FISH) in selected specimens.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15] The TMPRSS2-ERG gene fusion is the principle genomic alteration and a characteristic signature in approximately half of all prostate cancers. 14,[16][17][18][19][20][21][22][23] ERG regulates matrix metalloproteinases, thus influencing extracellular matrix remodeling and the invasive potential of malignant cells. [24][25][26][27] PTEN is among the most commonly mutated tumor suppressor genes in human cancer.…”
mentioning
confidence: 99%
“…[18][19][20] Several studies have shown anti-ERG antibody useful for prostate carcinoma, metastatic and primary, and prostatic intraepithelial neoplasias. [10][11][12]21,22 The detection of ERG is highly correlated with both ERG rearrangement by fluorescence in-situ hybridization and with ERG mRNA overexpression. 10,12,21 Similar to FLI1, ERG is also found to be expressed in both benign and malignant vascular tumors serving as a helpful marker for endothelial differentiation.…”
mentioning
confidence: 99%